2014
DOI: 10.1007/s12035-014-8824-4
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin Induces Insulin-like Growth Factor I Nuclear Translocation Regulating Its Levels in the Hippocampus

Abstract: Transthyretin (TTR) is the carrier protein of thyroxine (T4) and binds to retinol-binding protein (RBP)-retinol complex. It is mainly synthesized by both liver and choroid plexuses of the brain. Besides these properties, it has a neuroprotective role in several contexts such as Alzheimer’s disease (AD) and cerebral ischemia. Activation of insulin-like growth factor receptor I (IGF-IR) pathways and increased levels of TTR are associated with absence of neurodegeneration in an AD mouse model. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The expression level of TTR's in rats could be enhanced by progesterone via progesterone receptors both in vitro and in vivo (Quintela et al, 2011), and a similar upregulated effect of TTR caused by progesterone in mouse uterus was also observed (Diao et al, 2010). Furthermore, TTR could drive the nuclear translocation of insulin-like growth factor 1 receptor (IGF-1R) (Vieira et al, 2015), which could lead to functional changes in insulin-like growth factor 1 (IGF1). Interestingly, the stimulatory effect of IGF1 on GnRH release has been discovered (Hiney et al, 2009).…”
Section: Functional Analysis Of Degs In Pl Vs MLmentioning
confidence: 81%
“…The expression level of TTR's in rats could be enhanced by progesterone via progesterone receptors both in vitro and in vivo (Quintela et al, 2011), and a similar upregulated effect of TTR caused by progesterone in mouse uterus was also observed (Diao et al, 2010). Furthermore, TTR could drive the nuclear translocation of insulin-like growth factor 1 receptor (IGF-1R) (Vieira et al, 2015), which could lead to functional changes in insulin-like growth factor 1 (IGF1). Interestingly, the stimulatory effect of IGF1 on GnRH release has been discovered (Hiney et al, 2009).…”
Section: Functional Analysis Of Degs In Pl Vs MLmentioning
confidence: 81%
“…TTR was described as being involved in the regulation of insulin-like growth factor I (IGF-I) receptor in the hippocampus. TTR is able to increase IGF-I receptor levels, demonstrated in null and wild-type mice and in vitro-cultured cells [115]. Subsequently, it was found that TTR has a synergistic action with IGF-I over the IGF-I receptor, activating the Akt pathway, which is a specific IGF-I receptor signaling pathway [116].…”
Section: Transthyretin As a Gene Regulatormentioning
confidence: 99%
“…Interestingly, another upregulated transcript encodes transthyretin (TTR), a protein that is involved with transport of retinol in the plasma and which plays an important role in neuroprotection 57 as well as memory consolidation and neurogenesis in the hippocampus 58,59 . Furthermore, TTR has also been shown to upregulate hippocampal expression of insulin-like growth factor receptor I (IGF-IR) and its nuclear translocation 60 .…”
Section: Wt1 Target Genes: Immediate Early Genes Retinoic Acid-relatmentioning
confidence: 99%